2010
DOI: 10.1007/s00234-010-0801-7
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging of symptomatic nerve root of patients with lumbar disk herniation

Abstract: DWI is a potential tool for analysis of the pathophysiology of lumbar nerve roots compressed by herniated disks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…2A) demonstrated the feasibility of whole-body MR neurography with DWI that can visualize tissues with impeded diffusion, such as tumors, the brain, the spinal cord, and the peripheral nerves 56) . We found that diffusion-weighted MR neurography revealed that nerve swelling and transverse and mean ADC values were significantly greater in entrapped nerve roots in patients with lumbar disc herniation 39) and lumbar foraminal stenosis (Fig. 2B, C) 40) , suggesting demyelination and edema by slow compression caused by an increased degree of diffusion compared with that of normal tissue.…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 81%
See 1 more Smart Citation
“…2A) demonstrated the feasibility of whole-body MR neurography with DWI that can visualize tissues with impeded diffusion, such as tumors, the brain, the spinal cord, and the peripheral nerves 56) . We found that diffusion-weighted MR neurography revealed that nerve swelling and transverse and mean ADC values were significantly greater in entrapped nerve roots in patients with lumbar disc herniation 39) and lumbar foraminal stenosis (Fig. 2B, C) 40) , suggesting demyelination and edema by slow compression caused by an increased degree of diffusion compared with that of normal tissue.…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 81%
“…We excluded reviews, spinal cord studies and animal or in vivo studies. Our review identified a total of 35 articles: 24 DTI studies and 11 diffusionweighted MR neurography studies [31][32][33][34][35][36][37][38][39][40][41] . The number of lumbar nerve DTI studies has sharply increased in recent years ( Fig.…”
Section: Trends In Clinical Mr Neuroimaging Of Lumbar Nervesmentioning
confidence: 99%
“…Previous studies reported the common presence of neural oedema/ inflammation surrounding compromised nerve roots both in animals 38 and human beings. 39,40 In human beings, the location of the swollen lumbar nerve root corresponded with the pain locations indicated in pain drawings from patients with sciatica. 39 Therefore, researchers and clinicians have geared their management strategies towards therapeutic injections, 41,42 low velocity mobilisations, and high velocity thrust manipulative therapies, 43,44 all aimed at reducing LBP and nerve root irritation.…”
Section: Quantitative Findingsmentioning
confidence: 85%
“…An increase in ADC and a significant decrease in FA of compressed nerve roots compared with contralateral ones are detected in cases of symptomatic lumbar disk disease. This increase of ADC values is secondary to the venous congestion and edema that occurs in both pre-ganglionic and ganglionic segments of nerve lumbar roots (41). The decrease of FA values is also related to a loss of fiber anisotropy (Figure 11).…”
Section: A B D Cmentioning
confidence: 99%
“…Most clinical studies with DWN have been performed on brachial and lumbar plexus (17,41). In brachial plexus, DWN and DTN have demonstrated their ability to evaluate degenerative, compressive and traumatic conditions (42,43).…”
Section: Plexus Evaluation and Degenerative Disk Nerve Roots Entrapmementioning
confidence: 99%